2018
DOI: 10.1039/c7an01635b
|View full text |Cite
|
Sign up to set email alerts
|

In-cell NMR: from metabolites to macromolecules

Abstract: In-cell NMR of macromolecules has gained momentum over the last ten years as an approach that might bridge the branches of cell biology and structural biology. In this review, we put it in the context of earlier efforts that aimed to characterize by NMR the cellular environment of live cells and their intracellular metabolites. Although technical aspects distinguish these earlier in vivo NMR studies and the more recent in cell NMR efforts to characterize macromolecules in a cellular environment, we believe tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(111 citation statements)
references
References 146 publications
3
108
0
Order By: Relevance
“…In‐cell NMR spectroscopy is a tag‐free technique and allows the study, at atomic resolution, of structural properties of, for example, proteins and small DNA/RNA hairpins in cells. Therefore, the ASO was delivered into HEK 293T cells by electroporation, as used previously for solution‐state in‐cell NMR studies, to ensure robust uptake, and a classical in‐cell solution‐state NMR spectrum was acquired.…”
Section: Figurementioning
confidence: 99%
“…In‐cell NMR spectroscopy is a tag‐free technique and allows the study, at atomic resolution, of structural properties of, for example, proteins and small DNA/RNA hairpins in cells. Therefore, the ASO was delivered into HEK 293T cells by electroporation, as used previously for solution‐state in‐cell NMR studies, to ensure robust uptake, and a classical in‐cell solution‐state NMR spectrum was acquired.…”
Section: Figurementioning
confidence: 99%
“…For Hahn-echo based15 N R 2 measurement or CPMG-based 15 N R 2 relaxation dispersion experiments at near physiological conditions that aim at the characterization of µs-ms dynamics, we however recommend the use of a very low D 2 O content in the sample buffer, as low as 1% molar fraction or, alternatively, the use of an external deuterium reference. This applies both to in vitro or in-cell NMR experiments[84][85][86][87][88][89] and is most important for intrinsically disordered proteins that are characterized by low 15 N R 2 rate constants and where even small R ex contributions can lead to large changes in the measured 15 N R 2 rate constant.…”
mentioning
confidence: 99%
“…More recently, a bioreactor for measuring cellular metabolism by both fluorescence lifetime imaging microscopy and 13 C pyruvate MRI was reported (23) as well as an NMR tube bioreactor for 31 P cell viability measurements (24). Review articles on the use of bioreactors in NMR and MRI have been published recently (25,26). In this paper, we have shown that in vitro MRI of MCF-7/Her2 and MCF7/Neo4 cells at 9.4 T allows monitoring of the cellular response to treatment with Trastuzumab.…”
Section: Discussionmentioning
confidence: 99%